2023
DOI: 10.1038/s41419-023-05641-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fatty acid β-oxidation by leptin contributes to the proinflammatory characteristics of fibroblast-like synoviocytes from RA patients via LKB1-AMPK pathway

Abstract: Fibroblast-like synoviocytes (FLS) maintain chronic inflammation leading to joint destruction in rheumatoid arthritis (RA). Fatty acid β-oxidation (FAO) regulates cell function. Here, we aimed to investigate the effect of FAO enhanced by leptin on the characteristics of RA-FLS and elucidate the potential metabolic mechanism. Key enzymes involved in lipid metabolism were detected with qPCR in HSF, MH7A cell line and isolated RA-FLS treated with RA or healthy control (HC) serum. In some experiments, FAO inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We first reported that LKB1 modulates intracellular ROS production through SLC7A11 expression in RA as excessive ROS stimulate cell migration, and cell death is also promoted by oxidative stress. Although it was reported that leptin induces LKB1-AMPK-mediated inflammation of RA FLS [45], the LKB1-AMPK-SLC7A11-NOX4-ROS pathway has never been reported. Moreover, LKB1-deficient RA FLS were highly sensitive to oxidative stress, which may result in irreversible damage.…”
Section: Discussionmentioning
confidence: 96%
“…We first reported that LKB1 modulates intracellular ROS production through SLC7A11 expression in RA as excessive ROS stimulate cell migration, and cell death is also promoted by oxidative stress. Although it was reported that leptin induces LKB1-AMPK-mediated inflammation of RA FLS [45], the LKB1-AMPK-SLC7A11-NOX4-ROS pathway has never been reported. Moreover, LKB1-deficient RA FLS were highly sensitive to oxidative stress, which may result in irreversible damage.…”
Section: Discussionmentioning
confidence: 96%
“…MiR-126 overexpression decreased PIK3R2 protein, promoted proliferation, and decreased RA-FLS apoptosis, whereas miR-126 inhibition increased apoptosis. Additionally, miR-361-5p promoted FLS proliferation and inhibited apoptosis by targeting ZBTB10 in RA, and its possible mechanism of action involved increasing RA-FLS cells that secrete inflammatory factors ( 62 ).…”
Section: Altered Fls Metabolism and Intracellular Signaling Pathway T...mentioning
confidence: 99%
“… 7 In addition, peripheral blood monocytes (PBMCs) are thought to be the major source of osteoclasts in inflammatory environments, and osteoclasts derived from PBMCs show an enhanced bone resorption capacity. 316 Notably, the synovial fluid of RA patients contains mononuclear cells that express osteoclast‐related genes and can form osteoclasts spontaneously, indicating a heightened osteoclastogenic potential in RA. 7 These developments are further amplified by inflammatory cytokines such as TNF‐α and IL‐6, which activate the JAK–STAT signaling pathway and promote the differentiation of PBMCs into osteoclasts, leading to increased bone resorption and bone destruction.…”
Section: The Role Of Bone Homeostasis In Skeletal Diseasementioning
confidence: 99%